Wolbachia Utilizes lncRNAs to Activate the Anti-Dengue Toll Pathway and Balance Reactive Oxygen Species Stress in Aedes aegypti Through a Competitive Endogenous RNA Network - Mao, Wei; Zeng, Qin; She, Lingzhi; Yuan, Hao; Luo, Yuying; Wang, Renke; She, Yueting; Wang, Weifeng; Wang, Chaojun; Pan, Xiaoling (Frontiers in Cellular and Infection Microbiology, 2022)
Long non-coding RNAs (lncRNA), a class of RNA molecules without protein coding potential, are more than 200 nucleotides in length and widely present in a variety of species. Although increasing progress in regard to the determination of lncRNA function has been made in vertebrates, Aedes aegypti lncRNAs were only identified recently and the functions of few lncRNAs have been annotated so far. Herein, the genome-wide alteration of the lncRNA expression profile trigged by Wolbachia wAlbB infection was investigated by comparing A. aegypti Aag2 cells and W-Aag2 cells infected with Wolbachia wAlbB. Based on lncRNA sequencing, 3035 differentially expressed lncRNAs (DE lncRNAs) in total were identified upon Wolbachia infection, which were further validated by quantitative PCR. The constructed co-expression network of DE lncRNAs and mRNAs revealed that Wolbachia-induced DE lncRNAs were highly enriched in the oxidative phosphorylation pathway via trans-activity, according to the KEGG pathway enrichment analyses. In addition, the established competitive endogenous RNA (ceRNA) network identifies the DE lncRNAs enriched in cellular oxidant detoxification based on GO enrichment analysis. Furthermore, silencing of aae-lnc-7598, the significantly up-regulated lncRNA with the highest fold change induced by Wolbachia, caused a significant reduction of antioxidant catalase 1B (CAT1B) gene expression as well as the enhancement of mitochondrial reactive oxygen species (ROS) production in living cells. These findings indicate that Wolbachia manipulates lncRNA to balance intracellular ROS stress and ensure its endosymbiosis in host A. aegypti. Notably, the function assay demonstrated that aae-lnc-0165 suppressed by Wolbachia could induce expression of the REL1 gene, the key regulator of downstream Toll pathway, through the sequence-specific binding of aae-miR-980-5p, which contributes to the activation of Toll pathway. Moreover, the depletion of aae-lnc-0165 caused the suppression of mitochondrial ROS levels in living cells. Our data reveal that Wolbachia activates the anti-dengue Toll pathway through a lncRNA-ceRNA pattern. Taken together, our finding suggested that Wolbachia utilizes lncRNAs to activate host anti-dengue Toll pathway via a ceRNA network. Moreover, Wolbachia employs lncRNAs to ensure ROS homeostasis for ROS-based anti-dengue defense through either trans-regulation or the ceRNA network. This study identifies novel potential molecular biomarkers for prevention and control of epidemic dengue.